2008
DOI: 10.2108/zsj.25.195
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Antennal Lobe of the Ant Camponotus japonicus

Abstract: The carpenter ant, a social hymenopteran, has a highly elaborated antennal chemosensory system that is used for chemical communication in social life. The glomeruli in the antennal lobe are the first relay stations where sensory neurons synapse onto interneurons. The system is functionally and structurally similar to the olfactory bulbs of vertebrates. Using three-dimensional reconstruction of glomeruli and subsequent morphometric analyses, we found sexual dimorphism of the antennal lobe glomeruli in carpenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 21 publications
6
60
0
Order By: Relevance
“…A historical and often cited number of ϳ 1000 glomeruli in the hornet Vespa crabro [Hanström, 1928] is incorrect, as our closer inspection using confocal techniques revealed only about 250 glomeruli [Kelber, unpublished data]. Although we find a high number of glomeruli in all Attini, and also in other ant species such as Camponotus [Nishikawa et al, 2008;Zube et al, 2008], we cannot make predictions about the grade of social organization on the basis of glomerular number. Instead, we can assume that the high number of glomeruli, for instance in Ap.…”
Section: High Number Of Glomeruli and Its Potential Originmentioning
confidence: 54%
See 1 more Smart Citation
“…A historical and often cited number of ϳ 1000 glomeruli in the hornet Vespa crabro [Hanström, 1928] is incorrect, as our closer inspection using confocal techniques revealed only about 250 glomeruli [Kelber, unpublished data]. Although we find a high number of glomeruli in all Attini, and also in other ant species such as Camponotus [Nishikawa et al, 2008;Zube et al, 2008], we cannot make predictions about the grade of social organization on the basis of glomerular number. Instead, we can assume that the high number of glomeruli, for instance in Ap.…”
Section: High Number Of Glomeruli and Its Potential Originmentioning
confidence: 54%
“…The leafcutting Attini were the first and so far the only species in which an MG was found in the sterile worker caste [Kleineidam et al, 2005]. Until now, studies on the olfactory system in other species of ants did not reveal an MG in the female worker caste [Goll, 1967;Gronenberg and Hölldobler, 1999;Nishikawa et al, 2008]. It was shown by physiological and neuroanatomical data in the carpenter ant Camponotus floridanus that workers process information about the trail pheromone in regularly sized glomeruli [Zube et al, 2008].…”
Section: The Macroglomerulusmentioning
confidence: 99%
“…Within the female caste, C. fortis queens have a higher number of glomeruli than workers and males. Other studies in ants showed that the number of glomeruli in queens exceeded that in males, but was still lower or comparable to the numbers found in workers ( A. vollenweideri [Kuebler et al, 2010]; A. mellifera [Groh and Rössler, 2008]; C. japonicus [Nishikawa et al, 2008], and C. floridanus ). That this ratio is reversed in C. fortis might most likely be due to the especially low number of glomeruli in the workers rather than to a relatively larger number of glomeruli in the queens.…”
Section: Discussionmentioning
confidence: 65%
“…The behavioral repertoires of hymenopteran males are in general restricted, which in turn results in a reduced number of glomeruli compared to females ( Apis mellifera [Arnold et al, 1985;Brockmann and Brückner, 2001;Sandoz, 2006]; Harpegnathos saltator [Hoyer et al, 2005]; Camponotus floridanus ; Camponotus ja- ponicus [Nishikawa et al, 2008] , and Atta vollenweideri [Kuebler et al, 2010]). Analyses of the number of glomeruli in C. fortis males confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, this number was lower than that observed in species of parasitic insects such as Rhodnius prolixus, 28 (BARROZO et al, 2009), Aedes aegypti, 50 (IGNELL et al, 2005, and Anopheles gambiae, 60 (GHANINIA et al, 2007), and it was much lower than that observed in bees, 160 and ants, 215-460 (GALIZIA et al, 1999;SMID et al, 2003;NISHIKAWA et al, 2008;ZUBE et al, 2008). The number of glomeruli is generally considered to be correlated with the number of olfactory receptor neurons, which in turn determines the complexity of odors an arthropod can discriminate.…”
Section: Discussionmentioning
confidence: 83%